Causal associations between human gut microbiota and cholelithiasis: a mendelian randomization study - Li, Wei; Ren, Ao; Qin, Qiong; Zhao, Ling; Peng, Qiufeng; Ma, Ruidong; Luo, Shiqiao (Frontiers in Cellular and Infection Microbiology, 2023)
Background There was some evidence that gut microbiota was closely related to cholelithiasis, but the causal relationship between them remained unclear. In this study, we try to use Two-sample Mendelian randomization (MR) to clarify the potential causal relationship between gut microbiota and cholelithiasis. Methods Summary Genome-Wide Association Studies (GWAS) statistical data for gut microbiota was obtained from MiBioGen, and the data of cholelithiasis was obtained from UK Biobank (UKB). Two-sample MR analyses were performed to assess causalities between gut microbiota and cholelithiasis mainly using the inverse-variance weighted (IVW) method. Sensitivity analyses were used to determine the robustness of the MR results. Reverse MR analyses were performed to examine the reverse causal association. Results Our research results, based primarily on the IVW method, support the existence of a causal relationship between nine gut microbial taxa and cholelithiasis. We observed a positive association between Genus Butyrivibrio (p=0.032), Genus Lachnospiraceae_UCG_001 (p=0.015), Genus Ruminococcaceae_NK4A214_group (p=0.003), Genus Ruminococcaceae_UCG_011 (p=0.010) and cholelithiasis, while Order Rhodospirillales (p=0.031), Genus Actinomyces (p=0.010), Genus Phascolarctobacterium (p=0.036), Genus Rikenellaceae_RC9_gutgroup (p=0.023), Genus Ruminococcaceae_UCG_013 (p=0.022) may be associated with a reduced risk of cholelithiasis. We did not find a reverse causal relationship between cholelithiasis and 9 specific gut microbial taxa. Conclusions This is the first mendelian randomization study to explore the causalities between specific gut microbiota taxa and cholelithiasis, which may provide new ideas and a theoretical basis for the prevention and treatment of cholelithiasis in the future.